Geographical analysis of forest types based on a digital elevation model generated from synthetic aperture radar - Erdenebaatar, Nyamjargal; Damdinsuren, Amarsaikhan (Proceedings of the Mongolian Academy of Sciences, 2020)
This research aims to examine forest type distribution, based on slope and aspect maps, generated from synthetic aperture radar (SAR) data. The study is conducted over an area about 1564.9 km2 located in Khutag-Undur soum of Bulgan aimag (province), northern Mongolia. Sentinel-1 interferometric SAR images acquired on 5 and 17 October of 2020 are used to generate a digital elevation model (DEM). For a forest type classification, geocoded Sentinel-2 multispectral images acquired on 5 July and 27 September of 2019 are used. Initially, a DEM creation from the SAR data is performed and the slope and aspect maps are generated, following which geographical analysis is performed using slope, aspect and classified forest type maps. The result of the analysis shows that about half of the forested areas face the north-west, north and north-east directions. It also revealed that evergreen conifers are distributed on slopes of moderate degrees facing towards the south-east and south, whereas the deciduous conifers are mainly distributed on relatively steep slopes facing south-west, west and north-west.